Pengaruh Nadwah Usbu’iyyah terhadap Peningkatan Penguasaan Kaidah Bahasa Arab Mahasiswa Pendidikan Bahasa Arab IAIN Palopo. - Annisa Zahra Jabbar; Mawardi; Putra, H. Alfan (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
In learning Arabic, students of the Arabic language education program at the Islamic State Institute of Palopo cannot be separated from the factors that make learning Arabic challenging. This research examines the impact of the "Weekly Seminar" program on improving the acquisition of Arabic grammar among students in the Arabic Language Teaching Department at the State Islamic Institute of Palopo. The aim of this research is to determine the extent of the "Weekly Seminar" program's impact on enhancing the ability of students in the Arabic Language Teaching Department to acquire Arabic grammar. This research is quantitative and descriptive, and the methods of data collection include observation, interviews, and pre- and post-tests. The research sample consists of 19 students from the Arabic Language Teaching program at the State Islamic Institute of Palopo who participated in the "Weekly Seminar" program. The research results indicate the acceptance of H and rejection of H, with the calculated = 11.25 > 1.734, which means H is accepted and H is rejected. The conclusion is that there is a significant difference between the final scores (post-test) and the initial scores (pre-test). Also, from the mean, it is shown that (X2) = 78 > 61 (X1). Therefore, it can be concluded that the weekly seminar affects the improvement of Arabic grammar among students in the Arabic Language Teaching program at the State Islamic Institute of Palopo.